The Travels of Ibn Battuta - "Abd Al-Rahman Azzam" (Hood hood books: Cambridge, 1995)
In 1325, Ibn Battuta, a 21 year old scholar and religious judge, set off from his hometown in Tangier to perform the pilgrimage to Mecca. What was meant to take one year, took 30"--Cover
Keywords: Biographies - Book